THE LEGAL POSITION OF ISLAMIC BOARDING SCHOOL (PESANTREN) AS A REHABILITATION EFFORT FOR NARCOTICS ABUSE - Laksana, Andri Winjaya (International Journal of Law Reconstruction, 2021)
Islamic Boarding School or Pesantren is not only a place to teach religion, but also teaches other fields such as agribusiness and even rehabilitation for narcotics addicts. Rehabilitation is a process of integrated treatment activities to free addicts from drug dependence. Pesantren is one of the places that can be used to rehabilitate people who are addicted to drugs by using Islamic values that are usually applied to the students of Islamic boarding schools. This socio-legal research is descriptive in nature, strengthened by analysis of prescriptive interpretation. The results obtained from this study are the position of the Pesantren in the rehabilitation of drug abuse by applying two treatment methods for drug addicts, namely medical treatment and non-medical treatment. The rehabilitation process for narcotics addicts is the first, ablution, the second dzikr, the third five daily prayers in congregation, fourth, fasting on the Monday and Thursday, fifth or the last one is night prayer (Qiyamullail).